2019
DOI: 10.1108/ijem-11-2017-0318
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural teaching efficacy and cultural intelligence of teachers

Abstract: Purpose The purpose of this paper is to examine the impact of learning goal orientation and training readiness on teachers’ multicultural teaching efficacy and cultural intelligence. Design/methodology/approach A total of 182 responses from secondary schools in midwest and southern areas of the USA were analyzed using the hierarchical multiple regression. Findings The findings indicated that learning goal orientation positively influenced both teachers’ multicultural teaching efficacy and cultural intellig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Watkins and Noble (2016) argue that for teachers to have a positive attitude toward cultural diversity, their cultural intelligence capacity should be high. According to Kang et al (2019) teachers’ multicultural teaching efficacy positively influences their cultural intelligence. On the other hand, it has been determined that those with high cultural intelligence also have high self-efficacy and their professional performance has increases (Ang & Van Dyne, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Watkins and Noble (2016) argue that for teachers to have a positive attitude toward cultural diversity, their cultural intelligence capacity should be high. According to Kang et al (2019) teachers’ multicultural teaching efficacy positively influences their cultural intelligence. On the other hand, it has been determined that those with high cultural intelligence also have high self-efficacy and their professional performance has increases (Ang & Van Dyne, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cruz et al (2020) suggest revealing the factors which play a role in a teacher becoming culturally responsive. In the literature, there has been research related to teachers’ cultural intelligence (Kang et al, 2019; Petrović, 2011; Watkins & Noble, 2016) self-efficacy (Dilekli & Tezci, 2020; Schipper et al, 2020; Song et al, 2020) culturally responsiveness and competence (Karataş & Oral, 2015; Barnes & McCallops, 2019; Gaias et al, 2019; Szlachta & Champion, 2020). These research studies found relationships between certain of the related variables.…”
Section: Introductionmentioning
confidence: 99%
“…JSB is a complex, self-regulated behavior influenced by goal orientation (Noordzij et al, 2013;Payne et al, 2007). People with learning goals consider intelligence and ability as flexible qualities that can be continuously developed through effort and experience (Lin and Chang, 2005;Kang et al, 2019). The most attractive factor that places LGO in career research is that it is an individual preference and can be changed or trained to be changed (Van Hooft and Noordzij, 2009).…”
Section: H2 Pe Is Positively Associated With Preparatory Jsbmentioning
confidence: 99%
“…Research to date using CQS has been both strong and encouraging (Kang et al , 2019; Townsend et al , 2015; Collins et al , 2016; Schlägel and Sarstedt, 2016). A recent meta-analysis (Rockstuhl and Van Dyne, 2018) highlighted the predictive power of CQ and demonstrated the incremental validity and the value of the four factors, above and beyond latent CQ.…”
Section: Introductionmentioning
confidence: 99%